Pendidikan dan promosi kesehatan tentang diabetes mellitus - M. Arifki Zainaro (JOURNAL OF Public Health Concerns, 2021)
Health education and promotion about diabetes mellitus Introduction: Diabetes mellitus in Indonesia is a serious threat to health development. The 2010 NCD World Health Organization (WHO) global status report reports that 60% of the causes of death of all ages in the world are caused by non-communicable diseases. Diabetes mellitus is ranked 6th as a cause of death. About 1.3 million people die of diabetes and 4% die before the age of 70. Objective: After following this health education and promotion, participants are able to recognize the characteristics of Diabetes Mellitus and avoid Diabetes Mellitus. Method: Education and Health Promotion about Diabetes Mellitus with lecture method and question and answer discussion, with an overview of the implementation of activities. Results: Pre-test as many as 2 participants from 22 participants or 9% already know about diabetes mellitus. Participants can pay attention and give good feedback to the instructor and participants actively ask questions. Furthermore, after the activity was carried out, the authors evaluated the results using a post-test, namely there were 5 participants who were able to answer well. Conclusion: Of the 5 participants from 22 participants who were present were able to mention and understand the meaning of diabetes mellitus, mention and understand the risk factors and causes of diabetes mellitus, mention and understand the signs and symptoms of diabetes mellitus, mention and understand the complications of diabetes mellitus, remember and understand how to prevent it. diabetes mellitus, as well as remembering and understanding the care and treatment of diabetes mellitus.   Keywords: Diabetes Mellitus, the elderly, education and health promotion Pendahuluan: Penyakit diabetes melitus di Indonesia merupakan ancaman serius bagi pembangunan kesehatan. Laporan status global NCD World Health Organization (WHO) tahun 2010 melaporkan bahwa 60% penyebab kematian semua umur di dunia disebabkan oleh penyakit tidak menular. Diabetes melitus menduduki peringkat ke-6 sebagai penyebab kematian. Sekitar 1,3 juta orang meninggal karena diabetes dan 4% meninggal sebelum usia 70 tahun. Tujuan: Setelah mengikuti pendidikan dan promosi kesehatan ini, peserta mampu mengenali ciri penyakit Diabetes Melitus dan bisa menghindari terkena penyakit Diabetes Melitus. Metode: Pendidikan dan Promosi Keshatan tentang Diabetes Melitus ini dengan metode ceramah dan diskusi tanya jawab, berikut gambaran pelaksanaan kegiatan. Hasil: Pre test ada 2 peserta dari 22 peserta atau jika dipersentasekan sebanyak 9% yang sudah mengetahui tentang penyakit diabetes melitus. Peserta dapat memperhatikan dan memberi timbal balik yang baik pada penyuluh dan peserta aktif bertanya. Selanjutnya setelah dilakukakan kegiatan penulis melakukan evaluasi hasil dengan ,mnggunakan post test : terdapat 5 peserta yang mampu menjawab dengan baik Kesimpulan: Dari 5 peserta dari 22 peserta yang hadir dapat menyebutkan kembali dan memahami tentang pengertian diabetes melitus, menyebutkan kembali dan memahami tentang faktor resiko dan penyebab diabetes melitus, menyebutkan kembali dan memahami tentang tanda dan gejala diabetes melitus, menyebutkan kembali dan memahami tentang komplikasi diabetes melitus, menyebutkan kembali dan memahami tentang cara pencegahan diabetes melitus, dan menyebutkan kembali dan memahami tentang perawatan dan pengobatan diabetes melitus